PERANAN KEPALA SEKOLAH SEBAGAI EDUCATOR DI TAMAN KANAK-KANAK SE-KECAMATAN MINAS - Fadhilla Khaira; Rita Kurnia; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to describe the role of the principal as an educator and what are the obstacles in implementing it. To reveal the research focus, using a qualitative descriptive approach. Data were collected through interviews, observation, and documentation. In this study using data triangulation which was carried out simultaneously by researchers when conducting interviews, observations, and documentation of the selected data sources, the subjects of this study were: the principal. While the technique used in data analysis is interactive data analysis, through data reduction steps, data presentation, and drawing conclusions. The results of the study and the conclusions of the study indicate that: the role of the principal as an educator plays a role in its performance in the form of the principal always guiding, directing, and advising the teachers in the school. For school principals teaching and learning activities are the core of the education process and teachers are the main implementers and developers of the curriculum in schools, for that principals will pay attention to the level of competence of teachers, and principals always facilitate and encourage teachers to continuously improve their competencies. So that teaching and learning activities can run effectively and efficiently. The obstacles for now are in the form of health conditions, unstable networks and indirect training for teachers, because during the pandemic everything is online.Key Words: Principal, role, educator